Characterization of Foot‐and‐Mouth Disease Viruses Collected in Nigeria Between 2007 and 2014: Evidence for Epidemiological Links Between West and East Africa. Issue 6 (7th October 2016) - Ularamu, H. G.; Ibu, J. O.; Wood, B. A.; Abenga, J. N.; Lazarus, D. D.; Wungak, Y. S.; Knowles, N. J.; Wadsworth, J.; Mioulet, V.; King, D. P.; Shamaki, D.; Adah, M. I.
Summary: This study describes the molecular characterization of 47 foot‐and‐mouth disease (FMD) viruses recovered from field outbreaks in Nigeria between 2007 and 2014. Antigen ELISA of viral isolates was used to identify FMD virus serotypes O, A and SAT 2. Phylogenetic analyses of VP1 nucleotide sequences provide evidence for the presence of multiple sublineages of serotype SAT 2, and O/EAST AFRICA 3 (EA‐3) and O/WEST AFRICA topotypes in the country. In contrast, for serotype A, a single monophyletic cluster of viruses has persisted within Nigeria (2009–2013). These results demonstrate the close genetic relatedness of viruses in Nigeria to those from other African countries, including the first formal characterization of serotype O/EA‐3 viruses in Nigeria. The introductions and persistence of certain viral lineages in Nigeria may reflect transmission patterns via nomadic pastoralism and animal trade. Continuous monitoring of field outbreaks is necessary to dissect the complexity of FMD epidemiology in sub‐Saharan Africa.